Evaluasi User Experience Menggunakan Pendekatan Heuristic Pada Sistem Informasi Akademik Universitas Bina Darma Palembang - Ledy Armyoktora; Ari Muzakir (APTIKOM SUMSEL, 2021)
The Academic of Information System has been implemented at Bina Darma Unversity Palembang for a long time. The Academic of Information System is a web-based system facility that contains profiles and developments of student academic activities. The purpose of this study to evaluate sisfo to measure user perceptions and determine user satisfaction with Sisfo using a Heuristic Evaluation approach. From 39 questionnaire statements filled out by 98 respondents, it was found that Sisfo was in good condition and did not require repairs.